Factors influencing the customers' selection towards diminishing partnership home financing: an empirical study - Redzuan, Nur Harena; Abdul Razak, Dzuljastri (2014)

(untitled)
This research paper sought to investigate the selection criteria that influence customers in adopting Islamic home financing based on diminishing partnership concept. It is to determine the key factors among selection criteria of home financing, where the factors of ranking will be provided. A structured questionnaire was developed to the target population of existing home financing customers as well as potential home financing customers. 143 respondents were sampled from the target population using purposive sampling. The study is conducted by using Exploratory Factor Analysis (EFA). The finding shows that the factors influence customers to select the diminishing partnership home financing are in the following rank order: Shariah compliance, Promotion of societal well-being and equitable distribution, Overall view and preference, Method of computing and pricing, Concept of equity financing and Justice and equality.